PENGARUH FREE CASH FLOW, LEVERAGE RATIO, PROFITABILITY RATIO DAN ASIMETRIS INFORMASI TERHADAP EARNING MANAGEMENT (Studi Empiris Perusahaan Nonmanufaktur Sektor Infrastuktur, Utilitas dan Transportasi yang terdaftar di Bursa Efek Indonesia Priode 2017-201 - Ita, Masita; Fitrios, Ruhul; Odiatma, Fajar (I-Economics, 2020)
This study aims to determine (1) the effect of the free cash flow on the earning management (2) the effect of the leverage ratio on the the earning management (3) the effect of the profitability ratio on the the earning management (4) the effect of asymmetry information on the the earning management. the population of this study was nonmanufacturing sector utility, infrastructur and technology listed on the indonesian stock exchange in 2017 until 2019. The sample was chosen by purpose sampling method and obtained 31 companies with 71 observatio. the data used was secondary data obtained from www.idx.co.id. Data was analyzed by using panel data regression analysiswith spss 21. The result using partial test (t-test) showed that the variable free cash flow, profitability ratio, and asymetric information has effect on earning management with each level significance was 0.000, 0.021, dan 0.002. Unfortunately, this study failed to prove that the variable leverage ratio effect earning management with the level of singnificance was 0.090. Keyword: Free Cash Flow, Leverage Ratio, Profitability Ratio, Asymetric Information Earning Management.